KORELASI KECEMASAN DENGAN JENIS TENSION TYPE HEADACHE PADA MAHASISWA KEDOKTERAN ANGKATAN 2019 DI UNIVERSITAS ANDALAS - Dian Pertiwi Alty; Restu Susanti; Nita Afriani (Universitas Fort De Kock, 2020)
Tension type headache is the most common primary headache. Tension type headache can be triggered by anxiety. Anxiety often occurs in medical students, especially in new students. The aim of this study was to determine the correlation between anxiety and tension-type headache among medical students batch 2019 in Andalas University. This was an analytic study using cross-sectional design. Sampling was done by stratified random sampling technique and we obtained sample from 79 respondents. Headache diagnosis was based on the consensus of PERDOSSI 2018 which in accordance with International Classification of Headache Disorder 3rd Edition (Beta version). Anxiety was diagnosed by using Hamilton Rating Scale for Anxiety questionnaire that had been validated. The correlation between variabels was analyzed using Spearman Rho test. The results of univariate analysis showed that the majority of respondent were women (69,6%). The most common anxiety category was mild anxiety (57%). The most common tension-type headache type was infrequent type (62%). The results of bivariate analysis showed 8 sample (34,8%) which experienced moderate-severe anxiety had infrequent tension-type headache and 41 samples (73,2 %) which experienced mild anxiety also had infrequent tension type headache. This study showed that anxiety was positively correlated with tension-type headache (r=0,327 p=0.003)